Copper removal by Botryococcus braunii biomass with associated production of hydrocarbons - Areco, María del Mar (2013)
The goal of the present article is to evaluate the potential of copper(II) removal from acidic wastewater, associated with the production of hydrocarbons by the microalgae Botryococcus braunii. Results demonstrate that the growth of B. braunii is correlated with the hydrocarbon production as well as with alcalinization and copper removal from the medium. Even though B. braunii did not present high rates of copper adsorption, the increase in the pH of the media promotes the precipitation of the metal. In this way copper can be removed from solution by both, adsorption and precipitation. Results suggest that metabolic active biomass of B. braunii could be used for copper removal from solution while it produces appreciable quantities of hydrocarbons. This fact is very interesting in order to develop new remediation processes of waste water with coupled energy production